DIVORCE MEDIATION IN MINANGKABAU SOCIETY OF AL-AZHAR TAFSIR PERSPECTIVE - Fathan Fadhlullah; Hamdi. R, Khairul (Program Studi Hukum Keluarga Fakultas Syariah UIN Datokarama Palu, 2025)
Marriage which is ideally understood as an eternal bond, has not been fully realized in practice. Data from the Central Bureau of Statistics (BPS) indicate an increase in divorce rates in West Sumatra from 2020 to 2022. In 2020, there were 291,677 divorce cases, which rose to 447,743 cases in 2021 and further increased to 516,334 cases in 2022. Mediation, which is expected to be the most effective means of reducing divorce rates, has not yet yielded optimal results. This study aims to analyze divorce mediation in Minangkabau society from the perspective of Tafsir Al-Azhar. The topics discussed include: (1) the concept of divorce mediation in Supreme Court Regulation No. 1 of 2016 on Court Mediation, (2) the role of culture in divorce mediation practices within Minangkabau society, and (3) the concept of mediation from the perspective of Tafsir Al-Azhar. The research method used is a normative study with a descriptive analysis approach. The findings indicate that a culturally based approach in the mediation process is a strategic solution that mediators can utilize to optimize the function of mediation. Furthermore, integrating the cultural values of society with the Supreme Court's policies aligns with the mediation concept mandated in the Qur'an, as interpreted by Hamka in Tafsir Al-Azhar.